Identification and validation of reference genes for normalization of gene expression analysis using qRT-PCR in Megalurothrips usitatus (thysanoptera: thripidae) - Hou, Qingfang; Yuan, Linlin; Jin, Haifeng; Yan, Han; Li, Fen; Wu, Shaoying (Frontiers in Physiology, 2023)
Gene expression analysis by reverse transcription quantitative polymerase chain reaction (qRT-PCR) has been widely used in research including insects. The selection of appropriate reference genes is the key to obtaining accurate and reliable results from qRT-PCR. However, studies on the expression stability of reference genes in Megalurothrips usitatus remain lacking. In this study, qRT-PCR was used to analyze the expression stability of candidate reference genes in M. usitatus. The expression levels of six candidate reference gene transcription of M. usitatus were analyzed. GeNorm, NormFinder, BestKeeper, and ΔCt were used to analyze the expression stability of M. usitatus treated with biological factors (developmental period treatment) and abiotic factors (light, temperature, insecticide treatment, respectively). Comprehensive stability ranking of candidate reference genes was recommended by RefFinder. Results showed that ribosomal protein S (RPS) was the most suitable expression in insecticide treatment. Ribosomal protein L (RPL) was the most suitable expression at developmental stage and light treatment, whereas elongation factor was the most suitable expression in temperature treatment. RefFinder was used to comprehensively analyze the above four treatments, and the results showed that RPL and actin (ACT) showed high stability in each treatment. Therefore, this study identified these two genes as reference genes in the qRT-PCR analysis of different treatment conditions of M. usitatus. Ourfindings will be beneficial for improving the accuracy of qRT-PCR analysis for future functional analysis of the target gene expression in M. usitatus.